The sky is falling [digital theaters]. - Perry, T.S (IEEE spectrum)
This paper discusses some recent developments that are expected to put digital cinema in the mainstream. The hurdles that have prevented widespread adoption of digital cinema have finally been addressed when Digital Cinema Initiatives LLC, recently finalized a standard for this technology. Walt Disney Co. and Dolby Laboratories Inc. have agreed to pay the bill for complete digital cinema systems at 100 US theaters, banking on the intrinsic desirability of using digital technology in 3D projection. Digital projection makes 3D movies cheaper because instead of two film projectors, just one is required. Three-dimensional films done digitally also have the benefit of not being limited to 24 frames per second. The release of Disney's latest 3D animated movie, Chicken Little, showcases this capability.